2011
DOI: 10.1007/s10120-011-0101-x
|View full text |Cite
|
Sign up to set email alerts
|

Combination chemotherapy with S-1 plus cisplatin for gastric cancer that recurs after adjuvant chemotherapy with S-1: multi-institutional retrospective analysis

Abstract: BackgroundIt is unclear whether S-1 plus cisplatin is effective for patients with recurrent gastric cancer after adjuvant S-1 chemotherapy.MethodsWe retrospectively evaluated the efficacy of S-1 plus cisplatin in patients whose gastric cancer recurred after adjuvant S-1 chemotherapy.ResultsIn the 52 patients evaluated, the median duration of adjuvant S-1 chemotherapy was 8.1 months, and the median recurrence-free interval (RFI) since the last administration of adjuvant S-1 was 6.4 months. Among the 36 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Because the PFS was 2.3 months in recurrent gastric cancer with RFI of less than 6 months after adjuvant S-1 chemotherapy in the previous retrospective analysis [6], the threshold PFS was set at 2 months. The addition of XP was expected to increase PFS by 1 month.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the PFS was 2.3 months in recurrent gastric cancer with RFI of less than 6 months after adjuvant S-1 chemotherapy in the previous retrospective analysis [6], the threshold PFS was set at 2 months. The addition of XP was expected to increase PFS by 1 month.…”
Section: Methodsmentioning
confidence: 99%
“…After the results were reported from the JCOG9912 and SPIRITS trials, S-1 plus cisplatin (SP) became accepted as the standard treatment for patients with advanced gastric cancer (AGC) in Japan [4,5]. In a retrospective analysis of those patients by Shitara et al, SP was not shown to be effective in patients with recurrent gastric cancer, especially with a relapse-free interval (RFI) of less than 6 months after adjuvant S-1 chemotherapy [6]. In their report, compared with patients with RFI of ≥ 6 months, patients with RFI of < 6 months had a significantly lower objective overall response rate (ORR) (5.0 vs. 37.5%), shorter progression-free survival (PFS) (2.3 vs. 6.2 months), and shorter overall survival (OS) (7.3 vs. 16.6 months).…”
Section: Introductionmentioning
confidence: 99%
“…The response rate of treatment by S-1 + cisplatin is reportedly low (5 %) for patients who had recurrence within 6 months from completion of the S-1 adjuvant therapy when compared with the response rate for recurrences after 6 months from the completion (37.5 %) [50]. This result, found in a multi-institutional retrospective analysis, suggests that cancers that recur during or early after completion of an adjuvant chemotherapy are resistant to the drug used in that chemotherapy.…”
Section: Appendix: Clinical Questionsmentioning
confidence: 99%
“…We used RFI to compare patients with prior FP use and those without prior FP use. The previous studies that assessed re-challenge with a chemotherapeutic agent in other cancers reported that drug-free interval (time since last administration of the drug until relapse) is predictive of the efficacy of re-challenge [1012]. However, drug-free interval may be dependent upon the nature of the tumor (aggressive or indolent).…”
Section: Discussionmentioning
confidence: 99%
“…As such, some patients with ABC receiving capecitabine have a previous history of treatment with other FPs. Re-challenge of chemotherapeutic agents has been assessed in other cancers [1012]. However, aside from a few studies providing limited results, separately assessing patients either with or without prior use of FPs [4, 13], the efficacy of capecitabine in patients with ABC who have received FPs for the early breast cancer has not been studied sufficiently.…”
Section: Introductionmentioning
confidence: 99%